Baseline factors and early viral response (week 4) to antiviral therapy with peginterferon and ribavirin for predicting sustained virologic response in patients infected with hepatitis C virus genotype 1: A multicenter study1. Issue 1 (14th November 2012) - Toyoda, Hidenori; Kumada, Takashi; Shimada, Noritomo; Takaguchi, Koichi; Ide, Tatsuya; Sata, Michio; Ginba, Hiroyuki; Matsuyama, Kazuhiro; Izumi, Namiki
Abstract Both baseline predictive factors and viral response at week 4 of therapy are reported to have high predictive ability for sustained virologic response to peginterferon and ribavirin combination therapy in patients with hepatitis C virus (HCV) genotype 1. However, it is not clear how these baseline variables and week 4 response should be combined to predict sustained virologic response. In this multicenter study, the authors investigated the impact of baseline predictive factors on the predictive value of week 4 viral response. Receiver‐operating characteristic curve analyses were performed to evaluate the ability of week 4 reduction in HCV RNA levels to predict sustained virologic response in 293 Japanese patients infected with HCV genotype 1b. Analyses were performed in all patients and in patient subgroups stratified according to baseline variables. Overall, week 4 viral reduction demonstrates a high predictive ability for sustained virologic response. The sensitivity, specificity, positive predictive value (PPV), negative predictive value, and accuracy were higher than those of viral reduction at week 12. However, the best cut‐off levels differ depending on the baseline factors and they were lower in patients with unfavorable baseline predictors. When patients had the TG/GG rs8099917 genotype, the best cut‐off was markedly low with low PPV. Week 4 viral response can be a predictor of sustained virologic response in patients with HCV genotype 1 and is better than week 12 viral response. However, the cut‐off levels should be modified based on the baseline predictive variables. J. Med. Virol. 85:65–70, 2012. © 2012 Wiley Periodicals, Inc.